Comprehensive Geriatric Assessment in Men Aged 70 Years or Older with Localised Prostate Cancer Undergoing Radical Radiotherapy. Issue 9 (September 2017) - Osborne, G.E.C.; Appleyard, S.A.; Gilbert, D.C.; Jones, C.I.; Lorimer, C.; Villanueva, M.; Peasgood, E.; Robinson, A.; Nikapota, A.; Ring, A.
Abstract: Aims: Treatment decisions for men aged 70 years or over with localised prostate cancer need to take into account the risk of death from competing causes and fitness for the proposed treatment. Objective assessments such as those included in a comprehensive geriatric assessment (CGA) might help to inform the decision-making process. The aim of this study was to describe the CGA scores of a cohort of older men with prostate cancer, evaluate potential screening tools in this population and assess whether any CGA component predicts significant acute radiotherapy toxicity. Materials and methods: This was a prospective cohort study undertaking pretreatment CGA, Vulnerable Elders Survey (VES-13) and G8 assessment in patients aged 70 years and over with localised prostate cancer planned to undergo radical external beam radiotherapy. Results: In total, 178 participants were recruited over a 3 year period and underwent a CGA. Fifty-five (30.1%) participants were defined as having health needs identified by their CGA. Both VES-13 and G8 screening tools showed a statistically significant association with CGA needs ( P < 0.001 and X 2 = 15.02, P < 0.001, respectively), but their sensitivity was disappointing. There was no association between a CGA (or its components) and significant acute radiotherapy toxicity. Conclusions: Many older men with localised prostate cancer are vulnerable according to a CGA. The screening tools evaluated were not sufficiently sensitive to identify this group. CGA outcome does not predict for significant acute radiotherapy toxicity. Highlights: Many older men with localised prostate cancer are vulnerable according to a comprehensive geriatric assessment (CGA). CGA scores are not associated with significant acute radiotherapy toxicity. The impact of CGA scores on long term outcomes, including death from competing cases of mortality, is currently unknown.